The magician's land : a novel - Grossman, Lev. (New York, N.Y. : Penguen Books, 2014)
"Quentin Coldwater has been cast out of Fillory, the secret magical land of his childhood dreams. With nothing left to lose he returns to where his story began, the Brakebills Preparatory College of Magic. But he can't hide from his past, and it's not long before it comes looking for him. Along with Plum, a brilliant young undergraduate with a dark secret of her own, Quentin sets out on a crooked path through a magical demimonde of gray magic and desperate characters."--Provided by publisher.
Maps on endpapers.
Booklist starred
Library Journal
Publisher's Weekly
Booklist starred, May 2014
Kirkus Starred, June 2014
Keywords: College students -- Fiction; Magic -- Fiction; College students -- Fiction; Fantasy fiction; FICTION / Fantasy / Contemporary; FICTION / Fantasy / Epic; FICTION / General; Magic -- Fiction; Fantasy fiction